2021
DOI: 10.1371/journal.pone.0245331
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for adolescents with borderline personality disorder (BPD) or BPD features—A systematic review of randomized clinical trials with meta-analysis and Trial Sequential Analysis

Abstract: Objectives To review the effectiveness of psychological therapies for adolescents with borderline personality disorder (BPD) or BPD features. Methods We included randomized clinical trials on psychological therapies for adolescents with BPD and BPD features. Data were extracted and assessed for quality according to Cochrane guidelines, and summarized as mean difference (MD) with 95% confidence intervals (CI) for continuous data and as Odds ratios (OR) with 95% CI for dichotomous data. Risk of bias was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Although the pre-registered methods of the 2020 full review 8,11 Moreover, we concentrate on adult samples in this paper, adolescent samples being subject to other systematic reviews. 13,14 The review methods had been declared in the Cochrane protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Although the pre-registered methods of the 2020 full review 8,11 Moreover, we concentrate on adult samples in this paper, adolescent samples being subject to other systematic reviews. 13,14 The review methods had been declared in the Cochrane protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Robinson et al 16 reported no differences between treatment and control groups across 15 RCTs, with the exception of 1 study that compared CBT with treatment as usual. Storebø et al 17 found that DBT and MBT had some beneficial consequences for reducing self-harm among individuals with borderline personality disorder (BPD) but noted that these conclusions were based on low-quality evidence. Jørgensen et al 18 reported a significant association between DBT and self-harm at the end of treatment compared with control interventions but no association between cognitive analytic therapy or MBT and reductions in self-harm among adolescents with BPD or BPD features compared with treatment as usual, emphasizing the need for more high-quality clinical trials with larger samples.…”
Section: Introductionmentioning
confidence: 99%
“… 53 , 54 The evidence is summarized in a systematic review that showed limited evidence on the effect of MBT on adolescents when compared to control interventions. 58 Another RCT compared individual MBT treatment in adolescents to TAU and concluded that it may be effective in reducing self-harm and depression. 52 …”
Section: Dbt and Mbt: Two Of A Kind?mentioning
confidence: 99%